On the possibility to obtain the stress-strain curve for a strain-hardening material by spherical indentation. (1st January 2002) - Beghini, M.; Bertini, L.; Fontanari, V.
A numerical approach aimed at evaluation the stress-strain curve for metallic materials starting from the results of instrumented spherical indentation tests is presented. The spherical indentation for materials having different σ-ε curves was modelled by means of a parametric finite-elements analysis. It was studied as the shape of the indentation crater evolves with the load and it was verified that it depends on the strain-hardening and yield stress of the material. By means of an elaboration of these results, an iterative procedure was set up, which allows the σ-ε curve to be obtained with satisfactory accuracy for a large class of materials. The procedure was tested by interpreting a simulated indentation test on a typical structural steel, thus confirming its validity and accuracy.